Distribution of energy density of Dirac field in the closed universe - Sharma, SK; Khanal, U (Scientific World, 2011)
The behavior of the energy of the free Dirac field in the closed FRW universe has been looked at. It is generally expected that the comoving energy density for the particles is conserved. Although this expectation is true for the massless fields, it is not for the massive ones. So, there is a finite energy current in any finite sized volume of the universe. The energy current is positive throughout for lowest state, n = 0. For n = 1, however, there occurs negative energy flow near r = π/2. So energy flows out of the region. It may be expected that the two regions, on either sides may become disjoint over time, but this can be confirmed only after studying the time evolution. If confirmed, this could explain the process of fragmentation of large structures. Larger n appears to produce larger number of such density contrasts. Key words: Closed Universe; Dirac field; Energy Density DOI: http://dx.doi.org/10.3126/sw.v9i9.5492 SW 2011; 9(9): 1-3